Beneath the Surface: Mental Health and Harassment and Abuse of Athletes Participating in the FINA (Aquatics) World Championships, 2019. Issue 2 (2nd March 2022) - Mountjoy, Margo; Junge, Astrid; Magnusson, Christer; Shahpar, Farhad Moradi; Ortiz Lizcano, Edgar Ivan; Varvodic, Josip; Wang, Xinzhai; Cherif, Mohamed Yahia; Hill, Lee; Miller, Jim
Abstract : Objective: To assess the mental health and experience of sport-related harassment and abuse of elite aquatic athletes and to analyze it in relation to gender and discipline. Design: Cross-sectional study using an anonymous survey. Setting: The FINA World Championships 2019. Participants: Registered athletes in the disciplines of swimming, diving, high diving, water polo, artistic swimming, and open water swimming. Interventions: Athletes completed an online or paper-based questionnaire. Main Outcome Measures: The main outcome measures included screening for depression (10-item version of the Center for Epidemiological Studies Depression Scale revised), eating disorders (Brief Eating Disorders in Athletes Questionnaire), the subjective need for psychotherapeutic support, and the experience of sport-related harassment and/or abuse. Results: A quarter (24.6%) of the 377 responding athletes were classified as depressed and 2.5% as having an eating disorder. More than 40% of the athletes stated that they wanted or needed psychotherapeutic support. Fifty-one athletes (14.9%) had experienced harassment/abuse in sport themselves, and 31 (9%) had witnessed it in another athlete. The experiences of harassment and abuse ranged from unwanted comments about body or appearance (40.2%) to rewards in sport for sexual favors (2.5%) and rape (0.3%). Athletes who had experienced harassment/abuse in sport themselves had higher average scores for depression and eating disorders, and more of them felt they needed psychotherapeutic support. Up to a third would not talk or report to anybody if they saw or experienced harassment/abuse, and less than 20% would talk to an official for help. Conclusion: Targeted initiatives are required to address mental health issues and harassment and abuse in sport in the FINA aquatic disciplines.